REPRESENTASI CAPRES BONEKA DALAM MEME CAPRES BONEKA DI SOSIAL MEDIA - Dini Safitri (Universitas Bunda Mulia, 2015)
This study aims to describe the meaning of representation in the meme presidential candidate stuffed doll in social media. Political year 2014 was a year full of political